PENGEMBANGAN LKM TOPIK ADSORPSI LARUTAN PADA MATA KULIAH PRAKTIKUM KIMIA FISIKA 1 BERBASIS GREEN CHEMISTRY - Dilla, Belia Aisyah; ., Sanjaya; Sari, Diah Kartika (Jurnal Penelitian Pendidikan Kimia: Kajian Hasil Penelitian Pendidikan Kimia, 2025)
This development research aims to produce a Student Worksheet (LKM) on the topic of Solution Adsorption for the Physical Chemistry 1 practicum course based on Green Chemistry principles that is valid, practical. This research was conducted with students involved in the Chemistry Physics 1 practicum course. The development model used is the ADDIE model modified with Tessmer’s formative evaluation. Research data were obtained through expert reviews, practicality tests involving one-to-one evaluations and small group evaluations. The validity test results show that the LKM achieved a high level of validity with an average Aiken’s V coefficient of 0.91. The practicality test stage indicated that at the one-to-one evaluation stage, a percentage of 82.8% was obtained in the practical category, and at the small group evaluation stage, the percentage was 87.9% in the practical category. The results of this research show that the Green Chemistry-based student worksheet (LKM) on the topic of Solution Adsorption for the Physical Chemistry 1 practicum course meets the criteria of being valid, practical.